The Role of Education and Household Composition for Transitory and Permanent Income Inequality. Evidence from PSID Data - Johannes Ludwig (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
Transitory and permanent shocks to income have been shown to be important determinants of household consumption. This paper shows that there are significant differences in the development of transitory and permanent inequality of household income between demographic groups since the 1980s. Using data from the Panel Study of Income Dynamics the educational attainment and the composition of a household are found to play a key role. While permanent inequality increases steadily for educated households, it is flat over large parts of the sample period for the less educated households. Transitory inequality increases for all households headed by couples whereas it is constant for single households. Taken together, permanent shocks explain on average a larger part of the income variance of educated households whereas transitory shocks are relatively more important for the less educated. These results that can be explained by changes to skill demand and an increased female labor force participation are potentially able to explain empirical findings on the transmission of changes in income inequality to consumption inequality. – – Transitorische und permanente Einkommensschocks sind entscheidende Determinanten des Haushaltskonsums. Dieser Artikel zeigt, dass es seit Beginn der 1980er Jahre signifikante Unterschiede im Verlauf von transitorischer und permanenter Ungleichheit des Haushaltseinkommens zwischen verschiedenen Gruppen der US-Bevölkerung gibt. Mit Hilfe von Daten der Panel Study of Income Dynamics stellt sich heraus, dass der Bildungsabschluss und die Zusammensetzung eines Haushalts eine Schlüsselrolle spielen. Während permanente Ungleichheit für gebildete Haushalte stetig wächst, gibt es keinerlei Anstieg für weniger gebildete Haushalte über einen großen Zeitraum der Stichprobe. Transitorische Ungleichheit hingegen steigt für alle Paarhaushalte an, ist aber für Single-Haushalte konstant. Zusammengenommen erklären permanente Schocks durchschnittlich einen größeren Teil der Einkommensvarianz der gebildeten Haushalte, wohingegen transitorische Schocks im Vergleich bedeutender für weniger gebildete sind. Diese Resultate, die potenziell durch Veränderungen in der Nachfrage nach Qualifikationen und einer höheren Arbeitsmarktbeteiligung von Frauen hervorgerufen werden, sind in der Lage, empirische Befunde zu erklären, wie stark sich Veränderungen der Einkommensungleichheit auf Konsumungleichheit übertragen.
Keywords: D31; E24; 330; income inequality; transitory and permanent inequality; income dynamics